2011
DOI: 10.1007/s00167-010-1371-2
|View full text |Cite
|
Sign up to set email alerts
|

ACL reconstruction with “the original all-inside technique”

Abstract: With the improvement of knee arthroscopy during the past decades anterior cruciate ligament reconstruction has become a common procedure, with several surgical techniques described. The "original all-inside technique" for ACL reconstruction with manually drilled double half tunnels, allowing the use of one single tendon triplicated or quadruplicated and hopefully improving the quality of the contact area between graft and bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Cerulli et al 15 contended that all-inside techniques could cause less bone loss. Tsai et al 3 compared the efficacy of singlebundle versus double-bundle all-inside ACL reconstruction regarding knee kinematics and reported that double bundles provided advantages over a single bundle for rotational knee stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerulli et al 15 contended that all-inside techniques could cause less bone loss. Tsai et al 3 compared the efficacy of singlebundle versus double-bundle all-inside ACL reconstruction regarding knee kinematics and reported that double bundles provided advantages over a single bundle for rotational knee stability.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, several surgeons performed all-inside ACL reconstruction. [15][16][17][18][19] Because the allinside method helps to eliminate the dead space not occupied by the graft ligament, it can accelerate graft maturation and prevent tunnel enlargement. 20 In addition, this technique was shown to reduce postoperative pain because it results in minimal tibial bone loss and requires minimal skin incisions.…”
mentioning
confidence: 99%
“…Cerulli et al were the first to describe an all-inside ACL reconstruction technique that used a transforming retrograde drill to create the tibial and femoral sockets independently. 13 Femoral fixation was suspensory with a cortical button and tibial fixation was with a lowprofile tibial fixation device.…”
Section: Developmentmentioning
confidence: 99%
“…Nowadays radiological imaging upgrade can combine morphology and metabolism of ligaments like in PET-MRI, and some studies suggest that biological rearrangement, after ACL reconstruction, continues up to 24 months postoperatively 30 . However, in literature there are many attempt in order to modify tunnel widening, either from biological side, with the controversial use of PRP 31,32 , preserving ACL remnant 33 , hybrid graft 34 , alendronate 35 , manual drilling to reduce termical stress on bone 36 ; either from biomechanical side, improving tunnel position 37 and fixation systems stiffness. All these studies are conducted on little patient cohorts or on animal model, therefore it is desirable our little clinical experience would continue to also understand biological factors combined with biomechanical element.…”
Section: Discussionmentioning
confidence: 99%